1992
DOI: 10.1016/0735-1097(92)90171-i
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic dissection after successful coronary balloon angioplasty: No influence on restenosis or on clinical outcome in 693 patients

Abstract: These data indicate that a successfully dilated coronary lesion with an angiographically visible dissection is no more likely to develop restenosis, and is not associated with a worse clinical outcome, at 6-month follow-up than is a dilated lesion without visible dissection on the post-balloon angioplasty angiogram.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
1
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(34 citation statements)
references
References 46 publications
1
31
1
1
Order By: Relevance
“…Leimgruber et al 13 reported similar rates of angiographic restenosis in 986 patients with or without dissection, with the exception of those with final transstenotic gradients < 15 mmHg, who experienced better evolvement. Hermans et al 14 studied a prospective series of 693 patients with angiographic follow-up in 94% of cases, demonstrating that a successful angioplasty with residual dissection does not increase restenosis. Cappelletti et al 15 demonstrated that most dissections disappear during angiographic follow-up and that patients with uncomplicated dissections have lower restenosis rates than do those without dissections.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Leimgruber et al 13 reported similar rates of angiographic restenosis in 986 patients with or without dissection, with the exception of those with final transstenotic gradients < 15 mmHg, who experienced better evolvement. Hermans et al 14 studied a prospective series of 693 patients with angiographic follow-up in 94% of cases, demonstrating that a successful angioplasty with residual dissection does not increase restenosis. Cappelletti et al 15 demonstrated that most dissections disappear during angiographic follow-up and that patients with uncomplicated dissections have lower restenosis rates than do those without dissections.…”
Section: Discussionmentioning
confidence: 99%
“…Although atherosclerotic plaque rupture is a sine qua non condition for an effective coronary angioplasty, the incidence of angiographically visible dissections is 30% after balloon angioplasty and 5 to 10% after stent implantation [1][2][3][4]14 . The factors associated with coronary dissections after conventional angioplasty are angiographic calcification 2 , presence of a significant residual stenosis 6,7 , and the type of dissection according to the ACC 8 classification.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is still controversy about whether a relationship exists between dissection type defined by the NHLBI criteria and subsequent restenosis. 18,32,33) Leimgruber, et al initially raised the concept of "therapeutic" dissection in 1985. They reported a study, specifically focused on the relationship between dissection and restenosis, wherein 248 patients with angiographic evidence of intimal dissection were found to have a restenosis rate of 24% and 738 patients without dissection had a 30% rate of restenosis (p=0.08).…”
Section: Discussionmentioning
confidence: 99%